GENOME SEQUENCE ANALYSIS, RT-PCR DIAGNOSTICS AND CONSTRUCTION OF VIRAL PROTEIN-EXPRESSION CASSETES FOR KAZAKH ISOLATE OF ORDINARY AND ANDEAN STRAINS OF POTATO VIRUS S - Alexandrova , A.M.; Yeriskina , Y.A.; Nargilova , R.M.; Kryldakov , R.V.; Tokbergenova , Zh.A.; Pooggin , M.M.; Iskakov , B.K.; Karpova, O.V. (Eurasian Journal of Applied Biotechnology, 2022)
Potato virus S (PVS) belongs to the genus Carlavirus of family Betaflexiviridae with a positive-sense single-stranded RNA genome of 8.5 Kb. PVS is one of the most prevalent viruses of cultivated potatoes in Kazakhstan. Here we report phylogenetic analysis of complete genome sequences of Kazakh isolates of PVS from potato cultivars Fortuna and Ushkonyr, design of PVS strain-specific diagnostic PCR and construction of expression cassettes for conserved viral proteins from both isolates. The Fortuna and Ushkonyr isolates were found to share 79.9% nucleotide identity with each other and belong respectively to previously-defined ordinary and Andean strains of PVS. Based on analysis of conserved and variable regions of available PVS isolates, we designed primers for reverse transcription (RT)-duplex PCR to detect both strains in single and mixed infections and established their prevalence in Almaty region of Kazakhstan. Coding sequences of triple gene block proteins (25K, 12K, 7K), coat protein (34K) and cysteine-rich protein (11K) as well as methyltransferase, peptidase, helicase and RNA-dependent RNA polymerase domains of viral replicase were subcloned from both Fortuna and Ushkonyr genomic RNAs into the binary vector pBIN19 under the control of CaMV 35S promoter and nopaline synthetase terminator. These expression cassettes will be used to further investigate the biological properties and strain characteristics of viral proteins by their transient expression in plant cells and tissues or their stable expression in transgenic plants.